Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Perum Bulog Kanwil Lampung - Kesuma, Danesa Pramesya; Khairudin (Jurnal EMT KITA, 2023)
The purpose of this study is to look at how worker performance at the Perum Bulog Lampung Regional Office is affected by organizational culture. The population that is the focus of this research is all 48 employees who work at Perum Bulog Lampung Regional Office, so all of them are research objects. This research does not use a sample method, considering the limited number of employees in this company. Therefore, all 48 employees of the Perum Bulog Lampung regional office became research subjects. The data collection method in this research involves an observational approach and distribution of questionnaires via Google Form. The data obtained was then analyzed using validity, reliability, and simple linear regression tests. The research results show that organizational culture at the Lampung Regional Office does not have a significant influence on the performance of Perum Bulog employees at the Lampung Regional Office. This can be concluded from the results of the analysis, where the calculated t value (1.304) is lower than the t table value (2.013), and the significance level (0.199) is greater than 0.050. Therefore, the hypothesis (H1) in this study cannot be confirmed or supported.